Learning Motivation: How Effective is the Game-Based Learning Model Assisted by Articulate Storyline? - Afanin, Adilah; Baharudin, Baharudin; Hijriyah, Umi; Fitriani, Fitriani; Bahri, Saiful; Azizah, Nurul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Game-Based Learning with Articulate Storyline is a learning model combining interactive, game like activities with software tools to enhance the educational experience. The application’s interface, similar to Microsoft Powerpoint, creates a more engaging learning process, potentially increasing students’ motivation. This study aims to examine the impact of using Game- Based Learning with Articulate Storylire on the learning motivation of Islamic Education (PAI) students at SMP Negeri 3 Pardasuka. The research employs a quantitative method with a Quasi-Experimental Posttest-Only Control Group Design. Samples were chosen using Simple Random Sampling, and data were collected through validated learning motivation questionnaires. The results of normality test indicated a significance value of 0,200, showing that the data is normally distributed. The homogeneity test produced a significance value of 0,154, confirming the data is homogeneous. The t-test result was 0,674, which is greater than 0,05, meaning the null hypothesis (H0) is accepted, and the alternative hypothesis (H1) is rejected. In conclusion, this research demonstrates that implementing the Game-Based Learning model with Articulate Storyline does not have a significant effect on the learning motivation of students.